2023
DOI: 10.1017/s0007114523000363
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of different cut-off points of the NRS-2002 tool to identify nutritional risk in critically ill patients: a longitudinal study

Abstract: The American Society of Parenteral and Enteral Nutrition recommends nutritional risk (NR) screening in critically ill patients with NRS-2002 ≥ 3 as NR and ≥ 5 as high NR. The present study aimed to evaluate the predictive validity of different cut-off points of the NRS-2002 in the intensive care unit (ICU). A prospective cohort study was conducted with critically ill adult patients who were screened using the NRS-2002. Hospital and ICU length of stay (LOS), hospital and ICU mortality, and ICU readmission were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…We applied the NRS‐2002 cutoff points by ASPEN 2 : scores ≥3 (NRS‐2002_3) and ≥5 (NRS‐2002_5) classified patients as at NR and high NR, respectively. Additionally, we considered the cutoff point established by Stello et al, 15 classifying patients with ≥4 (NRS‐2002_4) as at NR.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…We applied the NRS‐2002 cutoff points by ASPEN 2 : scores ≥3 (NRS‐2002_3) and ≥5 (NRS‐2002_5) classified patients as at NR and high NR, respectively. Additionally, we considered the cutoff point established by Stello et al, 15 classifying patients with ≥4 (NRS‐2002_4) as at NR.…”
Section: Methodsmentioning
confidence: 99%
“…The best cutoff for NRS-2002 in this context is likely ≥4, based on a previous study by our research group, which showed superior prognostic value compared with other cutoff points (≥3 and ≥5). 15…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation